The Analysis of Networks Space Structures as Important Elements of Sustainable Space Development - Kowalczyk, Anna Maria (Environmental Engineering. Proceedings of the International Conference on Environmental Engineering. ICEE, 2017)
Space as the entirety of elements occurring within it and their configuration, is subject to analysis for purposes of optimizing activities connected with it, or generally speaking, optimal spatial management including predicting its future states and preventing spatial conflicts. Geospatial analysis is a complex process, the essential components of which are the collection, modelling and analysis of spatial data. Drawing proper conclusions is largely dependent on the type of spatial model developed. The author carries out the characterization of selected types of network models for purposes of spatial analysis in the sustainable development of space, providing examples of modelling various elements of space on the form of a network. She also touches on the aspect of hierarchy and scale-freeness in these models, as well as the possibility of predicting future states of space, and also using the properties of network models in decision processes to achieve sustainable development.